The Effect of Alpha Lipoic Acid on Pathogenesis of Experimental Nephrolithiasis and Epithelial Mesenchymal Transition - Kutlu, T; Kazak, F; Uyar, A (Journal of the Hellenic Veterinary Medical Society, 2023)
In this study, the effects of calcium oxalate (CaOx) crystal formation on the kidneys and the effect of alpha-lipoic acid (ALA) on this process were investigated in rats. The study consists of 6 groups with 10 rats in each group. Ethylene glycol (EG) and ammonium chloride (AC) (0.75% EG + 0.75% AC) were added to the drinking water of different groups for 7 or 14 days to induce nephrolithiasis. The effects of the CaOx on the kidneys and ALA (100 mg/kg/day/orally) on this process were investigated via histopathological, immunohistochemical, and biochemical methods. In the histopathological examination, EG+AC application for both 7 and 14 days caused crystal accumulation in the tubule lumens, cystically dilated tubules, and hydropic degeneration in the tubular epithelium. However, inflammatory cell infiltration was observed merely in 14 days. In the immunohistochemical examination, when EG+AC administration was applied for 14 days only, it caused expression of ED1, alpha smooth muscle actin (α-SMA), and vimentin in the tubulointerstitial areas. However, α-SMA and vimentin expression was not observed in tubular epithelial cells. Transforming growth factor beta-1 (TGF-β1) expression was also detected in the tubular epithelium and intertubular cells at 14 days. It was determined that ALA administration with EG+AC application reduced the crystal accumulation in the tubule lumens (p<0.001), the degeneration of the tubular epithelium (p<0.001), and the expression of TGF-β1. In addition, it was detected that ALA caused an increase in glutathione peroxidase (GPx) (p<0.001) and Catalase (CAT) (p>0.05) activities, which decreased with EG+AC application.